(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Type 2 diabetes mellitus, once considered a disease confined to adult populations, has emerged as one of the most pressing pediatric health challenges of the twenty-first century. Over the past two decades, the global incidence of this metabolic disorder among children and adolescents has risen dramatically, paralleling the escalating prevalence of childhood obesity and sedentary lifestyles. This comprehensive review examines the multifaceted nature of type 2 diabetes in pediatric populations, exploring its epidemiological patterns, underlying pathophysiological mechanisms, clinical presentation, diagnostic approaches, and evidence-based management strategies. The article further discusses the serious long-term complications associated with early-onset disease and outlines preventive interventions that hold promise for curbing this growing epidemic. Understanding these dimensions is essential for healthcare providers, educators, policymakers, and families working collaboratively to safeguard the metabolic health of future generations